Experimental investigations on optimisation of parameters to produce W-TiC composites using powder metallurgy route. (27th June 2019) - Sukumar, S.; Elatharasan, G.
In this research work, the effect of titanium carbide (TiC) in tungsten (W) matrix to be analysed. The W matrix composites contain different weight percentage (0, 4 and 8) TiC particles were produced by ball milling and powder metallurgy methods. The required quantity of powders were milled and compacted in a hydraulic press with a suitable punch and die. The sintering was done at a temperature of 1, 400°C for a period of three hours. The mechanical properties of the sintered composites were studied and reported. The SEM images of as received W and TiC power particles were reported. Taguchi analysis was used to discover the control of parameters and their relations on the output responses. Weight percentage of TiC has the most significant effect on hardness and flexural strength at the 95% confidence interval. Increasing the TiC addition increases the hardness and flexural strength of the composites.